2023
DOI: 10.1371/journal.pntd.0010482
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the risk of Rift Valley fever in Uganda using national seroprevalence data from cattle, sheep and goats

Abstract: Uganda has had repeated outbreaks of Rift Valley fever (RVF) since March 2016 when human and livestock cases were reported in Kabale after a long interval. The disease has a complex and poorly described transmission patterns which involves several mosquito vectors and mammalian hosts (including humans). We conducted a national serosurvey in livestock to determine RVF virus (RVFV) seroprevalence, risk factors, and to develop a risk map that could be used to guide risk-based surveillance and control measures. A … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Regarding brucellosis, goats had the highest prevalence than cattle. These findings align with previous research conducted in Uganda and Keny (Birungi et al, 2021;Kabami, 2023;Ndumu et al, 2021;Nyakarahuka et al, 2018aNyakarahuka et al, , 2023aNyakarahuka et al, , 2023bNyakarahuka et al, , 2023cNyamota et al, 2023;Tumusiime et al, 2023b).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Regarding brucellosis, goats had the highest prevalence than cattle. These findings align with previous research conducted in Uganda and Keny (Birungi et al, 2021;Kabami, 2023;Ndumu et al, 2021;Nyakarahuka et al, 2018aNyakarahuka et al, , 2023aNyakarahuka et al, , 2023bNyakarahuka et al, , 2023cNyamota et al, 2023;Tumusiime et al, 2023b).…”
Section: Discussionsupporting
confidence: 92%
“…The nationwide seroprevalence study by Nyakaruhuka et al showed that RVF was circulating in over 37/135 districts across the five regions in Uganda (Nyakarahuka et al, 2023c). An ecological niche model for Uganda also suggested that Isingiro district was a high risk area and the authors recommended surveillance activities to be targeted in such areas (Tumusiime et al, 2023a). In comparison with Kenya’s IgG RVF cattle seroprevalence picture (an indication to previous exposure to RVF), Owange et al reported 13.1% (183/1396) in 2014 (Owange et al, 2014a), Nanyingi et al reported 33.3% (95% CI [6.7–60]) in 2017, Bett et al reported 37.10% (30.72 – 43.84) in 2018.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Africa continues to face emerging global health problems, like outbreaks of Ebola and Marburg viruses [ 27 ], which require testing new medications and vaccines, but many ethical issues related to such studies remain unresolved [ 28 ]. In Uganda, the western and southwestern regions have experienced outbreaks of yellow fever [ 29 ], rift valley fever [ 30 ], measles [ 31 ], and the Ebola virus disease from border crossing with the neighboring Democratic Republic of Congo [ 32 ], creating a perfect environment that requires responses from public health experts and researchers. Furthermore, Uganda is facing an epidemiological transition in disease burden from communicable to non-communicable diseases [ 33 ].…”
Section: Introductionmentioning
confidence: 99%